Giant cornu cutaneum on the lower lip - Gábor Szabó; Gergely Vida; Gábor Fülöp (Hungarian Dental Association, 2020)
The 72-year-old male patient came to the oral surgical department of Kaposi Mór Educational Hospital in May 2018 complaining about a 15-centimetre big cornu cutaneum on the right side of the lower lip, which had been growing there for decades. In addition ulcerated mucous membrane lesions were recognisable on the left side of his lip. After examining and diagnosing the patient's mucous membrane lesions (CT, PET-CT-screening, scaling, radix removal) we deeply resected them from the intact part with linear excision. The results of the biopsy were Grade 1-2 squamous cell cc. of the lower (in the left third of the lip) as well as cornu cutaneum (in the right third of the lip). Thus according to the decision of the oncological team, the patient is under tight control (medical check-up every 3-6-9-12 month). Currently the patient is symptom and complaint-free, and his regular follow-up indicates unchanged status.